1992
DOI: 10.1080/0013188920340307
|View full text |Cite
|
Sign up to set email alerts
|

Skipping's for girls: children's perceptions of gender roles and gender preferences

Abstract: This short report presents a small-scale study which may be of interest to teachers and parents who are concerned about the extent to which primary school children's thinking shows, and is influenced by, gender stereotyping. As a descriptive study, the practical applications of its findings will depend upon the views of its readers as to whether or not they see it as part of their role to attempt to influence children's perceptions of gender.Four specially designed tasks were presented to children of between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
1
10
0
2
Order By: Relevance
“…Within the ER domain, it appears that male gender roles proscribe stoicism when experiencing sadness, whereas more latitude for sadness expression is granted to females (Brody & Hall, 2000), perhaps because the male role is seen as more rigidly proscribed than the female role (e.g., Henshaw, Kelly, & Gratton, 1992). When group norms exist, emotional expressivity that is consistent with those norms is likely to evoke positive social responses and promote social adaptation (Denham et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Within the ER domain, it appears that male gender roles proscribe stoicism when experiencing sadness, whereas more latitude for sadness expression is granted to females (Brody & Hall, 2000), perhaps because the male role is seen as more rigidly proscribed than the female role (e.g., Henshaw, Kelly, & Gratton, 1992). When group norms exist, emotional expressivity that is consistent with those norms is likely to evoke positive social responses and promote social adaptation (Denham et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examined whether the development of personalized conceptions of an enemy, if present, is paralleled by the emergence of an image of the same personal ‘enemy’, and what exactly such an image depicts. For instance, Hayes, Gershman, and Bolin (1980) showed that children least appreciate other children in their class when these children behave aggressively and do not respect rules. While these characteristics do not fit the previous definition of an enemy as a cognitive‐affective construct, the question as to whether such children are perceived as enemies was explored.…”
mentioning
confidence: 99%
“…Boys showed a different and more violent understanding of 'enemies' than girls. This finding may be due to gender-specific socialization processes such as parental and cultural encouragement of boys to show aggressive, independent, and boisterous behaviour (Henshaw, Kelly, & Gratton, 1992;Witt, 1997). Adopting such behaviour may partially account for the greater emphasis on war and physical violence by boys in their understanding of enemies.…”
mentioning
confidence: 99%
“…Age was considered as a covariate due to the significant differences in cognitive development and knowledge acquisition among the different primary education courses (Fischer and Bullock, 1984). Gender was also taken into consideration given the existence of previous evidence pointing to gender differences in the flexibilization of gender stereotypes (Smetana, 1986;Henshaw et al, 1992;Signorella et al, 1993;Fernández-Rouco et al, 2019), the acceptance of aggression and the type of aggression used (Askew and Ross, 1991;Crick et al, 1997;Subirats and Tomé, 2007), empathy (Tobari, 2003;Mestre et al, 2009), self-esteem (Watkins et al, 1997;Israel and Ivanova, 2002;Frisén et al, 2014), and emotional intelligence (Bar-On and Parker, 2000; Karma and Maliha, 2005;Ferrando, 2006). As a result, consideration was given to the role of gender in the effectiveness of the program.…”
Section: The Development Of a Program For The Prevention Of Partner Vmentioning
confidence: 99%